Coupled Temperature Sensitivity of Microbial Carbon and Nitrogen Use Efficiencies in Forest Soils on a Continental Scale - Yang Zhang; Lingrui Qu; Jian Wang; Yue Liu; Meixia Gao; Xu Wang; Fangying Qu; Edith Bai; Chao Wang (Global Change Biology, 2026)
Microbial carbon and nitrogen use efficiencies (CUE and NUE) are critical regulators of soil carbon and nitrogen cycling, with their temperature sensitivities playing a pivotal role in mediating biogeochemical feedbacks under global warming. However, how the temperature sensitivity ( Q 10 ) of CUE and NUE varies at different temperature ranges and whether their thermal responses are coordinated remains poorly understood. Here, we quantified the Q 10 of CUE and NUE in 55 soil samples collected from a ~4000 km latitudinal forest transect in eastern China. We further identified key drivers that shaped Q 10 variability from climatic, edaphic, and microbial factors. On average, Q 10 was 1.22 ± 0.08 for CUE and 1.46 ± 0.13 for NUE. However, both efficiencies exhibited clear temperature‐interval dependence: the mean Q 10 of CUE declined from 1.47 ± 0.14 at 12°C–20°C to 0.97 ± 0.08 at 20°C–28°C, while the mean Q 10 of NUE decreased from 2.00 ± 0.23 to 0.93 ± 0.09. The Q 10 values of CUE and NUE were strongly correlated across temperature ranges and positively associated with the Q 10 of microbial growth, indicating a coordinated thermal response governed primarily by growth‐based processes. At lower incubation temperature interval (12°C–20°C), variation in the Q 10 of CUE was primarily explained by soil stoichiometry and microbial community attributes, whereas under warmer conditions (20°C–28°C), climatic and edaphic constraints, particularly precipitation and soil N/P ratio, became dominant. Although microbial community attributes consistently explained most of the variance in the Q 10 of NUE, their influence weakened at higher incubation temperatures, paralleling the pattern observed for CUE and indicating a shift from biotic to abiotic control. Overall, these findings highlight that the temperature sensitivities of microbial CUE and NUE are tightly coupled, growth‐mediated, and strongly temperature‐context dependent, providing novel insights for improving predictions of soil carbon‐nitrogen turnover under climate warming.